فوائت (القاموس المحيط) للفيروزآبادي من الألفاظ في كتاب (التعليقات والنوادر) لأبي علي الهجري: جمع ودراسة - محمد علي، أحمد عبد الله (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research aims at collecting and studying the missing words in Al-Qamus Al-Muhit (Comprehensive Lexicon) by Fairuzabadi mentioned in Al-Ta'liqat wa Al-Nawader (Comments and Anecdotes) by Abu Ali' Al-Hagary. The researcher investigated the third part of Al-Ta'liqat wa Al-Nawader where the lexicographical meaning was missing. Al-Hagary provided the lexicographic underpinnings of the meaning while explaining the terms in his anecdotes such as the definition of the terms as well the abbreviation and type of words. He also provided explanations of the antithesis and synonyms as well as the morphological image. As far as the missing words were concerned, the study showed that around Forty words were unaccounted for. These included Seventeen verbs and Twenty-three nouns which were addressed such as qhadham, tamawwah, takaemaz while others were not addressed such as bhthal and bashkl. Interestingly, Fairuzabadi did not address words such as albidw and ikhtasham. The researcher utilised the analytical and descriptive approach, using the concept of alfawayat.